Enteric neurosphere cells injected into rectal submucosa might migrate caudorostrally to reconstitute enteric ganglia along the entire length of postnatal colon - Jeng-Chang Chen (Stem Cell Research & Therapy, 2022)
Abstract Background In enteric neural stem cell (ENSC) therapy for enteric neuropathy, the gut is ostensibly accessible via laparotomy, laparoscopy or endoscopy, whereas its elongated configuration and multilayered structures substantially complicate the targeting of ENSC delivery. This study aimed to evaluate the feasibility of ENSC delivery via trans-anal rectal submucosal injection. Methods ENSC transplantation was conducted in an immunologically compatible model of FVB/NCrl-Tg(Pgk1-EGFP)01Narl into FVB/N murine strain combination. Enteric neurospheres were mass-produced by the cultivation of dispersed enterocytes harvested from gestational day 14 FVB/NCrl-Tg(Pgk1-EGFP)01Narl murine fetuses. Dissociated neurosphere cells were injected into rectal submucosa of adult FVB/N mice after artificial prolapse of rectal mucosa. Ganglion reconstitution in recipients’ colon was examined by immunohistochemcal and immunofluorescence staining. Results Cell spreading and ganglion assembly in recipients’ colorectum were examined one week after transplantation. Donor ENSCs migrated rostrally within the colonic wall to intermuscularly repopulate the neighboring colorectum and assemble myenteric ganglia. It contributed to a chimeric state of myenteric plexuses with donor-origin ganglia of 41.2–67.5%. Two months later, transplanted ENSCs had undergone long-distance caudorostral migration almost up to the cecum to reconstitute myenteric and submucosal ganglia along the entire length of the colon. Conclusion This proof-of-principle study provided a viable justification for minimally invasive rectal ENSC transplantation to create long-term and long-range reconstitution of enteric ganglia. It opens up the new approach to ENSC delivery in laboratory animals and casts light on the feasibility of replacing damaged or replenishing missing enteric neurons by trans-anal rectal ENSC transplantation.